2009
DOI: 10.1242/dev.040204
|View full text |Cite
|
Sign up to set email alerts
|

TheC. elegansTailless/TLX transcription factornhr-67controls neuronal identity and left/right asymmetric fate diversification

Abstract: An understanding of the molecular mechanisms of cell fate determination in the nervous system requires the elucidation of transcriptional regulatory programs that ultimately control neuron-type-specific gene expression profiles. We show here that the C. elegans Tailless/TLX-type, orphan nuclear receptor NHR-67 acts at several distinct steps to determine the identity and subsequent left/right (L/R) asymmetric subtype diversification of a class of gustatory neurons, the ASE neurons. nhr-67 controls several broad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 46 publications
5
58
0
Order By: Relevance
“…Taken together, die-1 expression passes through several distinct phases: an early bilateral phase, likely controlled by bilateral ASE fate determinants such as che-1 and nhr-67 (Etchberger et al 2007;Sarin et al 2009); a restriction to ASEL that requires transient activity of the cog-1 homeobox gene; and a maintenance phase that requires ceh-36 and die-1 itself to promote expression in ASEL and fozi-1 to repress expression in ASER.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, die-1 expression passes through several distinct phases: an early bilateral phase, likely controlled by bilateral ASE fate determinants such as che-1 and nhr-67 (Etchberger et al 2007;Sarin et al 2009); a restriction to ASEL that requires transient activity of the cog-1 homeobox gene; and a maintenance phase that requires ceh-36 and die-1 itself to promote expression in ASEL and fozi-1 to repress expression in ASER.…”
Section: Resultsmentioning
confidence: 99%
“…(C) Testing the effect of 39UTR replacement on functional derepression of die-1 and cog-1 gene activity. Based on previous work, derepression of die-1 function in ASER is expected to result in a transformation of ASER to ASEL (Johnston et al 2005), while derepression of cog-1 function in ASEL is expected to result in a transformation of ASEL to ASER (Chang et al 2003;Johnston et al 2005;Sarin et al 2009). Transgenic animals containing reporters with wild-type 39UTRs or replaced 39UTR (as shown in panel A) were assayed for their ability to convert cell fate, as assessed with the ASER fate marker gcy-5Tgfp (ntIs1), which is expressed in ASEL if ASER fate is induced (left table) and repressed in ASER if ASEL fate is induced (right table).…”
Section: Discussionmentioning
confidence: 99%
“…These reporter genes are fully functional and rescue the cog-1 and die-1 mutant phenotypes, respectively (data not shown). The left/right asymmetric regulation of cog-1 and die-1 is functionally relevant since ectopic expression of cog-1 in ASEL converts ASEL into ASER and overexpression of die-1 converts ASER to ASEL (Chang et al 2003;Johnston et al 2005;Sarin et al 2009; data not shown).…”
Section: Sequence Features Of the Three Regulatory Elementsmentioning
confidence: 93%
“…Hobert , 2003;Johnston et al, 2006;Ortiz et al, 2006;Ortiz et al, 2009; PierceShimomura et al, 2001;Poole and Hobert, 2006;Sarin et al, 2009;Sarin et al, 2007;Uchida et al, 2003;Yu et al, 1997). In both cases, asymmetry contributes to being able to distinguish between attractive chemicals.…”
Section: Development 682mentioning
confidence: 99%
“…In both AWC and ASE neurons, the left and right neurons of a pair are functionally different from each other, with different patterns of gene expression. ASE neurons express multiple genes asymmetrically, including nuclear proteins, transcription factors, guanylyl cyclase sensory receptors and microRNAs (Chang et al, 2004;Chang et al, 2003;Etchberger et al, 2009;Johnston and Hobert, 2003;Johnston et al, 2006;Ortiz et al, 2006;Ortiz et al, 2009;PierceShimomura et al, 2001;Poole and Hobert, 2006;Sarin et al, 2009;Sarin et al, 2007;Uchida et al, 2003;Yu et al, 1997). In both cases, asymmetry contributes to being able to distinguish between attractive chemicals.…”
Section: Types Of Left-right Asymmetry In C Elegans Nervesmentioning
confidence: 99%